Positive Effects of Videogame Use on Visuospatial Competencies: The Impact of Visualization Style in Preadolescents and Adolescents - Milani, Luca; Grumi, Serena; Di Blasio, Paola (Frontiers in Psychology, 2019)
Use of videogames (VGs) is almost ubiquitous in preadolescents’ and adolescents’everyday life. One of the most intriguing research topic about positive effects of VG use is about the domain of visuospatial competencies. Previous research show that training with videogames enables children and adolescents to improve their scores in visuospatial tests (such as mental rotation of shapes and cubes), and that such training could overcome gender differences in these domains. Our study aimed at (1) verifying the positive effects of videogame use in the visuospatial domain both for male and female adolescents and preadolescents and (2) verifying whether the visualization style (2D or isometric 3D) of the VG has an influence about the positive effects of gaming. Six measures of visuospatial competency were administered to 318 preadolescents (mean of age = 13.94 years, range 10-18) prior and after a 3-day training with 2D and 3D Tetris. Results indicate that (1) gaming on the whole has slight positive effects both for males and females in enhancing visuospatial competencies, at least in the short term, and (2) it seems that participants who used the videogame with 2D graphics obtained greater improvements in the mental rotation domain while the participants who used the videogame with 3D gobtained greater improvements in the spatial visualization domain. However, a general learning effect between T1 and T2 was measured, which was found regardless of Experimental condition, indicating that the effect of training with videogames can be less relevant than expected.